Ethical Decision-Making in Entrepreneurial Dentistry: An Exploratory Conceptual Framework Informed by Romanian Healthcare Studies - George Dumitru Constantin; Alexandru Cucui-Cozma; Ioana Veja; Crisanta-Alina Mazilescu; Roxana Oancea (Dentistry Journal, 2026)
Background/Objectives: Dental graduates make clinical decisions shaped by ethical principles, legal obligations, patient expectations, and private-practice economics. This study synthesized empirical findings from Romanian healthcare education and practice and proposes an exploratory model for teaching ethical decision-making in entrepreneurial dentistry. Methods: Exploratory conceptual framework development informed by four previously published Romanian healthcare studies examining business-ethics attitudes using the Attitudes Toward Business Ethics Questionnaire (ATBEQ), moral reasoning using an adapted Defining Issues Test-2 (DIT-2; 242 valid cases), scenario-based ethical decision-making (n = 244), and ethical reasoning profiles derived from the joint administration of the ATBEQ and 35-item scenario questionnaire (n = 277). Results: “It depends” accounted for 47.8% of scenario responses. Students and practitioners differed regarding vaccination of healthcare workers, risk-based insurance contributions, and organ-market policy (chi-square, df = 2, uncorrected). Practitioners endorsed law-oriented arguments more strongly but weighted patient autonomy more heavily at end of life. Idealism/Legalism showed an isolated exploratory association with fewer conditional responses (B = −0.69, 95% CI −1.28 to −0.11, p = 0.021); however, the overall regression model was not statistically significant and had low explanatory power (R2 = 0.04, adjusted R2 = 0.02, p = 0.08). Four ethical reasoning profiles were identified. Conclusions: The G.D.C. framework is a theory-informed, hypothesis-generating educational framework derived from mixed Romanian healthcare samples. It has not been validated specifically in entrepreneurial dentistry and requires prospective, dental-specific validation.